2011
DOI: 10.26634/jpsy.5.1.1494
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Teachers� Collective Efficacy And Student Achievement At Economically Disadvantaged Middle School Campuses

Abstract: The purpose of this study was to examine the relationship between the collective efficacy of teachers and student achievement at economically disadvantaged middle school campuses. The population of the study consisted of Texas campuses that served economically disadvantaged students and received a campus rating of Exemplary or Academically Unacceptable for two consecutive years, according to the Texas Education Agency (TEA). The data shows that significant differences exist between the collective efficacy of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
2
3
0
Order By: Relevance
“…Bandura (1993) was the first to generate interest in this area by demonstrating that the effect of perceived CTE on student achievement was stronger than the link between socioeconomic status and student achievement. Consistent findings have been reported in a number of other studies since (Goddard et al , 2015; Ramos et al , 2014; Sandoval et al , 2011). In 2011, Eells conducted the first meta-analysis, synthesizing 26 available and relevant studies, in order to quantify the correlation between CTE and student achievement.…”
Section: Evidencing the Enabling Conditions For Collective Teacher Efficacysupporting
confidence: 91%
See 1 more Smart Citation
“…Bandura (1993) was the first to generate interest in this area by demonstrating that the effect of perceived CTE on student achievement was stronger than the link between socioeconomic status and student achievement. Consistent findings have been reported in a number of other studies since (Goddard et al , 2015; Ramos et al , 2014; Sandoval et al , 2011). In 2011, Eells conducted the first meta-analysis, synthesizing 26 available and relevant studies, in order to quantify the correlation between CTE and student achievement.…”
Section: Evidencing the Enabling Conditions For Collective Teacher Efficacysupporting
confidence: 91%
“…Research shows that when teachers share the belief that through their collective actions they can positively influence student outcomes, student achievement increases (Bandura, 1993; Eells, 2011; Goddard et al , 2015; Ramos et al , 2014; Sandoval et al , 2011). Bandura (1993) was the first to generate interest in this area by demonstrating that the effect of perceived CTE on student achievement was stronger than the link between socioeconomic status and student achievement.…”
Section: Evidencing the Enabling Conditions For Collective Teacher Efficacymentioning
confidence: 99%
“…CTE has received increased attention from educational researchers since the time Bandura (1993) demonstrated that the effect of perceived collective efficacy on student achievement was stronger than the link between socio-economic status and student achievement. Consistent findings have been reported in a number of studies since (Goddard et al , 2000; Hoy et al , 2002; Moolenaar et al , 2012; Ramos et al , 2014; Sandoval et al , 2011). For example, Goddard et al (2000) found that CTE was a more significant predictor of student achievement than socio-economic status in both mathematics and reading in elementary schools.…”
Section: Collective Efficacysupporting
confidence: 88%
“…In a study examining mathematics achievement in high schools, Hoy et al (2002) found that collective efficacy “was more important in explaining school achievement than socio-economic status” (p. 89). Sandoval et al (2011) examined the relationship between CTE and student achievement at economically disadvantaged middle school campuses and found that the efficacious campuses could “impact student achievement through their belief in their colleagues’ ability to impact student achievement regardless of the students’ background and socioeconomic status” (p. 21). Moolenaar et al (2012) also found that “perceived collective efficacy was positively associated with increased language achievement, above the influence of socio-economic status” (p. 257) in elementary schools.…”
Section: Collective Efficacymentioning
confidence: 99%
“…Conversely, a positive association was observed between the programme engagement outcome and the proportion of residents within a community who did not have a high school diploma. Low educational attainment of community residents may have reflected a lack of educational opportunities and resources within the mothers' communities (Sandoval, Challoo, & Kupczynski, ). In these communities, family support programmes such as home visiting may have filled an important gap when expectant mothers and families with young children had less opportunity to address child development and parenting questions to allies within their communities (Daro et al, ; Weissbourd, ).…”
Section: Discussionmentioning
confidence: 99%